Neuroimaging Findings in Patients with Covid-19 in Indonesia - Sadikin, Cindy; Meryana, Meryana; Besin, Valentinus; Saelan, Yanna (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Background: Covid-19 caused by the SARS-CoV-2 virus has spread worldwide, including Indonesia. Neurological manifestations has also been reported in Covid-19 positive patients. Yet documentation of their neuroimaging findings are lacking, especially in Indonesia. Objective: To understand neuroimaging findings in Covid-19 positive patients Methods: An observational study from medical record of Covid-19 positive patients in our hospital who developed abnormal neurologic manifestations and were followed up by neuroimaging examination from May to August 2020. Covid-19 positive diagnosis was confirmed from nasopharyngeal swab using the Real Time Polymerase Chain Reaction (RT-PCR). Neurological examination was performed by a neurologist, who then referred patients for neuroimaging examination using CT or MRI. Radiological expertise was performed by a radiologist. Results: A total of 288 patients who are Covid-19 positive from nasopharyngeal RT-PCR swab admitted to our hospital from May to August 2020. Ten patients (3.5%) had abnormal neurologic manifestations and further neuroimaging examination follow up. Range of age 33-72 years old and slight male predominance (60%). Frequent clinical symptoms were decreased consciousness (40%), altered mental status (30%) and tremors (20%). Neuroimaging findings were large vessel occlusion (30%), vasculitis (20%), post hipoxic leucoencephalopathy (10%), basal ganglia encephalopathy (10%), non specific small vessel ischemia changes and negative findings (30%). Most patients were discharged with clinical improvement (60%), while 40% mortality rate were seen in patient with large vessel occlusion (30%) and vasculitis (10%). Conclusion: Neuroimaging findings in Covid-19 positive patients were large vessel occlusion (LVO), vasculitis, post hipoxic leucoencephalopathy and basal ganglia encephalopathy Keywords: Covid-19, neurological, manifestation, neuroimaging